Effect of Short Sleep Duration on the Risk of Cardiovascular Diseases: A Meta-Analysis - Hidayat, Anas Rahmad; Siswatibudi, Harpeni; Purwokusumo, R. Haryo Nugroho (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Understanding the impact of short sleep duration on cardiovascular disease incidence is crucial for comprehending its potential health implications. This study aimed to analyze and estimate the magnitude of the effect of short sleep duration on the risk of cardiovascular disease incidence based on similar previous primary studies.Subjects and Method: This research is a systematic review and meta-analysis conducted by following the PRISMA flow diagram and PICO model. Population: general population without prior cardiovascular diseases, Intervention: short sleep duration, Comparison: adequate sleep duration, and Outcome: the Incidence of cardiovascular diseases. The process of searching for articles through Google Scholar, ProQuest, and PubMed journal databases by selecting articles published from 2010 to 2024. The keywords used include: